EDUKASI ANAK-ANAK DALAM PENGOLAHAN SAMPAH PLASTIK DENGAN DAUR ULANG MEMBUAT KARYA ECOBRIK SEBUAH KURSI - Fadilah, Muhammad Ilham; Wulan, Ananda Ayu; Ningsih, Widya; Karina, Karina; Artianta, Wenny; Febriyana, Kailah; Barokah, Nadya; Silvia, Silvia; Sabil, Ridho; Guna, Shubhan Tri; Bangsawan, Muhammad Ali (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The increase in population activity directly contributes to the accumulation of waste, especially plastic waste that is difficult to decompose and has a negative impact on human health and the surrounding environment. Ecobrik emerged as one of the solutions to overcome this waste problem. This plastic waste management method uses used plastic bottles filled with various types of plastic waste to the brim, then compacted into hard materials. From this ecobrik method produces the work of a chair.